Les mots maoris dans The Bone People de Keri Hulme : exotisme et intimisme - Alice Braun (Revue LISA)
Although Keri Hulme’s the bone people is now recognised as forming part of the literary canon in New Zealand, its publication in 1985 met with some controversy, particularly around the author’s choice to claim herself a Maori in culture and ethnicity. Part of the debate focused around Hulme’s decision to compile a glossary of the Maori words used in the text, a device which carries a significant literary and political weight in the context of post-colonial studies. This paper shows how the use of Maori words in the English text may be accused of participating in a strategy of “exoticisation” of the text, though they still have a strong symbolic meaning within the economy of the narrative. They materialise a whole community’s alienation from nature and from their own culture, and they also allow Hulme to delineate new forms of love and family ties that are yet to be invented.